2014
DOI: 10.1155/2014/830657
|View full text |Cite
|
Sign up to set email alerts
|

Catalase Activity in Brown Mussels (Perna perna) under Acute Cadmium, Lead, and Copper Exposure and Depuration Tests

Abstract: Brown mussels (Perna perna) were exposed to cadmium (Cd), lead (Pb), and copper (Cu) concentrations under acute exposure and exposure-depuration tests for the estimation of biochemical biomarker catalase (CAT). The acute tests showed accumulated Cd, Pb, and Cu inPerna pernacorrelated linearly with the exposure concentrations (R2=0.794,R2=0.891, andR2=0.985for Cd, Pb, and Cu, resp.). The results of CAT increased significantly in tissues of treatment mussels after 72 h exposure when compared to control. The valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 40 publications
1
7
1
Order By: Relevance
“…Our findings contradicted with previous publication, which showed that Cu accumulation has no correlation with GST activity in different tissues of this species collected from the Nhue-Day River [8]. However, our results were in line with Cu and Pb but not with Cd treatment for Brown Mussels (Perna perna), which showed a high correlation (R>0.92, p<0.01) of the CAT activity in tissues with the metal accumulation [15]. Together with these findings, our data might suggests enzyme activity was changed not only by the accumulation of metal but also by other factors such as the form of metal chemicals, characteristics of organisms, and the living environment as reported in previous study [4,12,13].…”
Section: Correlation Between Enzymatic Activity and Bioaccumulationcontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings contradicted with previous publication, which showed that Cu accumulation has no correlation with GST activity in different tissues of this species collected from the Nhue-Day River [8]. However, our results were in line with Cu and Pb but not with Cd treatment for Brown Mussels (Perna perna), which showed a high correlation (R>0.92, p<0.01) of the CAT activity in tissues with the metal accumulation [15]. Together with these findings, our data might suggests enzyme activity was changed not only by the accumulation of metal but also by other factors such as the form of metal chemicals, characteristics of organisms, and the living environment as reported in previous study [4,12,13].…”
Section: Correlation Between Enzymatic Activity and Bioaccumulationcontrasting
confidence: 99%
“…Our data displayed not only the activation but also the repression of enzyme activity by HMs exposure, suggesting that the activity changes might be related to the accumulation of HMs in the organism. Many scientists have been concerned about the relationship between HMs accumulation and enzyme activity in various species [8,14,15]. To examine whether the accumulation of Cu, Pb, and Cd affects alteration in the activity of CAT and GST, the Pearson's correlation test for the relationship between enzyme activity and HMs accumulation in muscle was performed (data not shown).…”
Section: Correlation Between Enzymatic Activity and Bioaccumulationmentioning
confidence: 99%
“…Boudjema et al. () have also reported that CAT activity was restored after the depuration period in brown mussels Perna perna after acute exposure to Cd, Pb, and Cu. Therefore, the fish tissues analyzed in the present study were able to adapt to Pb concentrations of 120 mg/kg efficiently, and this concentration might indicate the peak capacity of Starry Flounder against the dietary Pb exposure to resist oxidative stress.…”
Section: Discussionmentioning
confidence: 91%
“…The overproduction of H 2 O 2 is countered by an increase of CAT activity, which it is part of biochemical adjustments against the ROS generation in the digestive gland. Similarly, other authors had demonstrated that SOD and CAT activities increase in diverse invertebrate’s species such as gastropod [ 48 ], mussels [ 49 ], clam [ 50 ] and scallops [ 51 ] exposed to heavy metals and mixtures of polyaromatic hydrocarbons under acute exposure.…”
Section: Discussionmentioning
confidence: 94%